Analysis of Enhanced Oil Recovery Based on Well Patterns and Injection Volume Using the Continuous CO2 Injection Method - Oktaviani, Ajeng Purna Putri; Silaban, Nanda Nicholas; Jannoke, Ludovika (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This study examines how the continuous CO2 injection method can improve oil recovery based on well patterns and injection volumes. The increase in oil recovery is observed using a number of well pattern scenarios, each with injection volume sensitivity. CMG-GEM is the software used in this study to simulate the different scenarios. A homogeneous reservoir model, grid data, reservoir fluid data, and reservoir data are among the data needed for this study. Four-spot, five-spot, nine-spot well patterns are taken into consideration in this research scenario. For each well pattern` the injection volumes that will subsequently be used as a reference for the injection rate at the injection well are one HCPV, five HCPV, ten HCPV, and twenty HCPV. According to the study’s findings, the inverted nine-spot well pattern with an injection volume of twenty HCPV scenario improves oil recovery more than the four-spot, five-spot and nine-spot well patterns.